Obesity awareness among elders living in rural area: a household survey - Maycon Sousa Pegorari; Alisson Fernandes Bolina; Darlene Mara dos Santos Tavares (Universidade Federal de Santa Catarina, 2017)
The acceptance of the disease is essential to health self-care, elder's awareness regarding obesity is suggested to influence their search for health services, and consequently, in obesity's treatment. This study aimed to verify obesity awareness of elders living in rural areas and associated socioeconomic and demographic factors. We conducted a cross-sectional household survey with 562 individuals, who were older than 60 years and were rural residents from a Brazil southeast city. The identification of obesity awareness was consisted in the agreement between the self-referred obesity and the diagnosis criteria using the body-mass index >27Kg/m². The associated socioeconomic and demographic factors were: gender, age range, marital status, education and income. Descriptive statistical analysis, Kappa index and logistic regression (p <0.05) were conducted. The highest percentage of elders were men (53.6%), 60├ 70 years old (62.6%), married (67.8%), studied for 4|-8 years (40.0%) and with an individual monthly income of one minimal wage (45.7%). The prevalence of obesity according to the body-mass index was 34.7% and the self-referred 15.1%, which was classified as regular agreement by the Kappa coefficient (k= 0.232; p<0.001). The majority of the elders with obesity were not aware of  this condition (64.6%), with higher odds ratio for men than for women (OR=2.34;CI=1.29-4.77). We found high obesity prevalence among elders residents in the rural area, who did not recognize themselves with this condition. Moreover, elderly men presented lower obesity awareness than women.